2017
DOI: 10.1016/j.scr.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Generation of induced pluripotent stem cells derived from an autosomal dominant polycystic kidney disease patient with a p.Ser1457fs mutation in PKD1

Abstract: Autosomal dominant polycystic kidney disease is one of the most prevalent forms of inherited cystic kidney disease, and can be characterized by kidney cyst formation and enlargement. Here we report the generation of a Type 1 ADPKD disease iPS cell line, IBMS-iPSC-012-12, which retains the conserved deletion of PKD1, normal karyotype and exhibits the properties of pluripotent stem cells such as ES-like morphology, expression of pluripotent markers and capacity to differentiate into all three germ layers. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Our research team applied iPSC technology to decipher the direct or indirect effect of the mutation gene on the cardiovascular phenotype of ADPKD cases. We first generated three ADPKD patient-derived iPSC lines and confirmed their pluripotency as reported [ 17 , 59 , 60 ]. We then efficiently differentiated the iPSCs toward cardiomyocyte-like cells, which were characterized as ventricular cardiomyocytes.…”
Section: Ipsc-based Human Disease Modeling: Kidney Differentiation An...supporting
confidence: 60%
“…Our research team applied iPSC technology to decipher the direct or indirect effect of the mutation gene on the cardiovascular phenotype of ADPKD cases. We first generated three ADPKD patient-derived iPSC lines and confirmed their pluripotency as reported [ 17 , 59 , 60 ]. We then efficiently differentiated the iPSCs toward cardiomyocyte-like cells, which were characterized as ventricular cardiomyocytes.…”
Section: Ipsc-based Human Disease Modeling: Kidney Differentiation An...supporting
confidence: 60%
“…Preserving the naturally occurring genetic mutations as well as the genetic background of their parental somatic cells, hiPSCs can be applicable to disease/patient-specific modeling. Genetically characterized hiPSCs have been efficiently derived from patients with autosomal dominant polycystic kidney disease (ADPKD) and autosomal recessive PKD (ARPKD), Alport syndrome, systemic lupus erythematosus, and Wilms' tumor and patients undergoing hemodialysis [58,[92][93][94][95][96][97]. In addition, mouse models commonly used in previous studies could not fully recapitulate human genotypes and phenotypes [98,99].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…We then demonstrated that our engineering system can also be adapted to model human PKD by constructing similar tubules using cells that were isolated from a patient with ADPKD and confirming the beneficial effects of 2DG and berberine. Previous studies have successfully derived iPSC lines from PKD patients [ 28 , [72] , [73] , [74] ]. Moreover, Xia and colleagues showed that PKD-derived iPSCs can differentiate into UB progenitors and integrate into reaggregating mouse kidneys to form chimeric UB structures [ 28 ].…”
Section: Discussionmentioning
confidence: 99%